Ospemifene plus fractional CO2 laser: a powerful strategy to treat postmenopausal vulvar pain. (3rd May 2020) - Murina, F.; Felice, R.; Di Francesco, S.; Nelvastellio, L.; Cetin, I.
Abstract: This study is a single-center, retrospective analysis of postmenopausal women presenting with dyspareunia and vulvar pain, aiming to evaluate relative effectiveness of vestibular CO2 laser therapy as a treatment. Three monthly sessions of laser were performed to each patient and thereafter a three-months follow-up was stablished. A total number of 72 patients undergoing vestibular laser treatment were recruited from patient files in the period between 2016 and 2018. Among these, 39 women also received a concomitant treatment with ospemifene (60 mg/day) during the study period. There was a statistically significant reduction of all the symptoms in both groups up to the three month follow-up. Regarding dryness and dyspareunia, the relief tent to be more prominent in the ospemifene + laser group at all follow-ups and remained statistically significant at three-month follow-up. Specifically, vestibular dryness was significantly lower in the ospemifene + laser group compared with the laser treatment group (−87% vs  − 34%, respectively), and the vestibular health score started declining faster in the ospemifene + laser group. Although, additional research is needed to understand the mechanism of action, our data shows that a combination regimen of laser and ospemifene may improve clinical effectiveness for long-term treatment of symptoms associated with the under-recognized genitourinary syndrome of menopause.